PERANCANGAN SISTEM LAPORAN KEUANGAN DAN PAJAK BERBASIS MISCROSOFT EXCEL SEBAGAI UPAYA OPTIMALISASI ADMINISTRASI KEUANGAN UMKM CORNDOG MOZA - dea pratama Nanda (LP2M Politeknik Jambi, 2026)
UMKM Corndog Moza still faces challenges in managing financial administration and taxation due to manual and unstructured transaction recording, which results in suboptimal financial reporting and tax calculation. This study aims to design a Microsoft Excel–based financial and tax reporting system as an effort to optimize the financial administration of UMKM Corndog Moza. The research method used is descriptive qualitative with a system design approach, employing observation, interviews, and documentation techniques. The results show that the designed Microsoft Excel–based system is able to facilitate more organized, automated, and accurate financial transaction recording, as well as generate income statements, statements of financial position, and Final Income Tax (PPh Final) calculations for UMKM in accordance with applicable tax regulations. Therefore, the implementation of a Microsoft Excel–based financial and tax reporting system can improve the efficiency of financial administration and support tax compliance for UMKM Corndog Moza.